Le développement du jeu éducatif ABDI (Aventure à Bali : Devinez l’Icône) comme support d’apprentissage dans le cours de Français du tourisme - Dewayani, Lupita; Purwani, Neli (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This research developed the game ABDI (Adventure in Bali: Guess the Icon) to support learning French for Tourism at Universitas Negeri Semarang. This media development aims to improve students’ ability to present Balinese tourist and cultural attractions in French. Using the ADDIE model, this game goes through the stages of analysis, design, development, implementation, and evaluation. The results show that the ABDI game effectively achieves learning objectives, increasing understanding of Bali tourism and practicing French presentation skills. Students gave positive responses, making ABDI an innovative and compelling learning medium.